Verbal Bullying Dalam Media Sosial Ditinjau Dari Perspektif Penyimpangan Prinsip Kesantunan Berbahasa - Ni Nyoman Ayu Suciartini; Ni Luh Putu Unix Sumartini (Jayapangus Press, 2018)
This study aimed at describing, 1) form of verbal bullying which emerges in social media, 2) deviation principle of linguistic politeness in verbal bullying cases which arise in social media, and 3) the impact of verbal bullying which emerges in social media. In achieving this goal, researchers used a descriptive-qualitative research design. Subject of this study is a user of social media accounts in facebook, path, bbm, twitter, yahoo, and so on. In general, the object of this study is verbal bullying in social media viewed from the perspective politeness principle. Data collections are colected through documentation method, interviews, and the questioner. The data obtained were analyzed by descriptive qualitative includes three phases, namely, (1) data reduction, (2) the presentation of the data, and (3) verification and drawing conclusions. These results indicate that: (1) the form of verbal bullying which emerges in social media expressed with the intent to be funny, advise, sarcastic, insulting, threatening, (2) forms of verbal bullying deviation in terms of violating the principle of linguistic politeness maxims of wisdom, sympathy, of agreement (compatibility), and awards, (3) The impact of verbal bullying that arise in social media has positive and negative influences.